Design Solutions Utilizing the Staggered-steel Truss System - Cohen, Michael P. (Engineering Journal, 1986)
During the conceptual design stages of most building projects, the structural engineer must consider many different factors before selecting the final structural system. While some basic building properties such as height, shape, usage, etc. lead the structural designer toward certain proven systems, it is not infrequent that architectural constraints, owner requirements and/or building location render these systems unacceptable. Other factors which enter into the selection process include: local economic conditions (both of materials and labor), construction schedule, design loads (vertical and lateral), building behavior and occupant comfort, foundation considerations and coordination with mechanical systems. While these general considerations are required on all projects, each specific building usually presents the designer with an additional set of its own unique problems. This paper outlines the conceptual design and selection process by which the staggered-truss system of structural framing was selected for one particular project. The subsequent design process encountered problems, and their associated resolutions are also reviewed.